Low incidence and prevalence of hepatitis C in two cohorts of HIV pre‐exposure prophylaxis adherence interventions in men who have sex with men in Southern California. Issue 7 (12th April 2022) - Hassan, Adiba; Agustin, Harold Glenn San; Burke, Leah; Kofron, Ryan; Corado, Katya; Bolan, Robert; Landovitz, Raphael J.; Dubé, Michael P.; Morris, Sheldon R.
Abstract: HIV pre‐exposure prophylaxis (PrEP) has been associated with incident hepatitis C virus (HCV) infection in men who have sex with men (MSM) due to decreased condom use. We examined rates of HCV among MSM and transgender women at high‐risk of HIV on PrEP in Southern California using data from two trials (NCT01761643 and NCT01781806). Five of 599 participants (0.84%, 95% CI, 0.27–1.93) had HCV antibodies detected at entry. Factors associated with HCV seropositivity included being older ( p = .002) and lower education level ( p < .001). HCV‐positive participants had no reported cases of sexually transmitted infection (rectal, urethral or pharyngeal gonorrhoea and/or chlamydia) at entry while HCV‐negative participants had a prevalence of 18% (95% CI, 15%–21%). There were no significant differences in substance use and sexual risk behaviour between HCV‐positive and HCV‐negative participants 1–3 months prior to entry. Among early PrEP adopters, incident HCV did not occur despite ongoing condomless intercourse. Screening intervals for HCV in MSM on PrEP should be led by a risk behaviour assessment.